Efeito da distribuição de massa de objeto no desempenho de cianças de diferentes idades em tarefa de precisão - Ana Paula Pereira de Melo (2011)
Fitts Task captures the essential aspects of manual functions that require the solution of the conflicting speed-precision demand. Two targets are touched continuous and reciprocally with maximum precision and least time. The difficulty of this task (DI) is characterized by the size of the targets and by the distance between them. The time spent to successfully execute a pointing movement increases in situations of greater difficulty. According to the literature, the objects resistance to manipulative movements is informative of its functional opportunities to perform specific actions. The functional utility of objects seems to be associated with individuals sensibility to perceive the effect of objects mass distribution to perform a specific action. To the present date, the effect of the inertial properties of objects used in the context of the Fitts task has not been investigated. The objective of the present study was to investigate the effect of the inertial properties of rods on the performance of children with normal development of 5, 8 and 11 years of age, in a precision task with two levels of difficulty. A total of 37 children were asked to touch reciprocally two targets, maintaining the requisites of maximum speed and precision. This task was performed with rods firmly held by the dominant hand, with an attached mass positioned at 10, 20 and 30 cm of the axis of movement (i.e., hand), characterizing rods of high, intermediate and low adequacy, respectively. The difficulty of the Fitts task was defined by pairs of targets of 3 cm (i.e., task of high difficulty) and of 10 cm (i.e., task of medium difficulty). The outcome variable was mean time of movement (MT) to perform each cycle (i.e., sequence of touch to one target, to the other target and return to the previous) throughout one trial. Mean TM for the two trials performed by each child on each experimental condition was used for analysis. A mixed 3 x 3 x 2 ANOVA with one between-subject factor (age: five, eight, eleven) and two within-subject factors (Rod adequacy: high, intermediate and low; and target size: large and medium) was used to evaluate the main effects age, target and rod adequacy as well as the interaction effects age x target, age x rod adequacy, target x rod adequacy and age x target x rod adequacy. Post-hoc comparisons were used to characterize the significant effects. The results demonstrated that the rods perceived in previous studies as more adequate for precision tasks did in fact enhance childrens performance. However, this effect was different in the different age groups and task conditions. In the eleven-year-old group, there was no significant effect of rod adequacy on MT, regardless of the size of the target used. In the eight-year-old group, significant differences in MT, between the high and low adequacy rod conditions were observed for both medium (p= 0,006; corrected = 0,008) and large targets (p= 0,005). Finally, in the five-year-old group, there was a marginal difference in movement time between the high and low adequacy rod conditions, but only for the large target (p= 0,009). The results suggest that childrens performance on the Fitts task was the result of a process, supported by perceptual information, that promoted a fit between the muscle-skeletal systems and the objects dynamic in order to meet the tasks demands.